Licenciamento ambiental de parques eólicos no Estado da Paraíba: uma análise socioambiental - Cartaxo, Ryan de Brito (2019)
The production of electricity by alternative sources has taken on a new impetus in Brazil since 2001, when the largest rationing of electric energy occurred in the country's history. This crisis was mainly caused by the mismatch between installed capacity and investment in generation, which demonstrates the fragility of being exclusively dependent on the energy matrix based on hydroelectric plants. In response to this scenario, the Federal Government created the Incentive Program for Alternative Energy Sources (PROINFA). The proposal was to implement projects with 3300 MW of capacity, diversify the Brazilian energy matrix, seek regional solutions with the use of renewable energy sources. The Northeast and North regions are considered the areas with the best potential for wind power generation in Brazil. In this context, it has been that Paraíba stands out in the production of alternative energy. Based on this premise, this research sought to analyze the environmental impacts, environmental licensing processes of wind farms in the State of Paraíba in two geographically, climatically distinct regions that are the Coastal and the Sertão. In the Litoral, located in the Municipality of Mataraca, the wind mills Millenium and Vale dos Ventos, in the hinterland, in the Municipalities of Junco do Seridó and Santa Luzia, Canoas Park composed of Lagoa 1 and Lagoa 2. Based on an exploratory research , based on a bibliographical and documentary survey, also using the interview as a technique through a semi-structured questionnaire, aimed to contextualize wind energy in Brazil in a more macro perspective, so that it could be understood its development in the Northeast region and, consequently, in Paraíba, in order to better characterize the spaces. In a dialogue with this context, a documentary survey that could subsidize the discussion about regulation, supervision of environmental licensing, added to an investigation that aimed to identify the positive and / or negative impacts on the resident population in the surroundings of the wind farms. From the point of view of results, it is understood that the licenses are within the expectations of the current regulation, as well as the impacts caused are positively more relevant than the negative ones, given that for the residents there is an awareness of local development, although there is also an estimated expectation regarding the utilization of the workforce of the residents. Thus, this study aims to contribute to the reflection about the production of knowledge of renewable energies, more specifically, wind energy, especially in the region of Paraíba, geographical breakdown of this research.